Clinical and ultrasonographic correlation of changes in the equine axial skeleton with thoracic and pelvic lameness detected by objective evaluation (Research, Society and Development, 2023)
Cervical and thoracolumbar changes are commonly found in sports animals and may be related to biomechanical alterations, driving movement, and the type of saddle used. The objective of this study was to characterize the correlation between clinical and ultrasonographic findings of the equine axial skeleton with objective evaluation lameness in the thoracic or pelvic limbs. A total of 76 horses of the mounted cavalry with an average of ten years of age, divided between castrated males and females of indeterminate breeds, were submitted to clinical, ultrasonographic and objective evaluations. The evaluated variables were classified in scores from 0 to 4, for later statistical analysis spearman correlation through the RStudio® software. The animals were classified into six groups according to the objective, clinical and ultrasonographic changes. A weak positive correlation was observed between the objective evaluation variable in relation to the clinical (r = 0.1, p > 0,05) and ultrasonographic (r = 0.1, p > 0,05) evaluation variables. In the present study, it was impossible to consider the correlations statistically significant since the p-value was higher than the significance level of 5%. Therefore, the associated evaluation of the axial and appendicular skeleton is of fundamental importance in the clinical routine to investigate musculoskeletal changes. This was demonstrated in the present study, where 68.42% (n=52) presented both clinical and ultrasonographic changes of the axial skeleton concomitantly with thoracic and/or pelvic lameness.